القراءات الشاذة عند السمين الحلبي في كتابه الدر المصون ن في علوم الكتاب المكنون: جزء تبارك أنموذجا: دراسة نظرية مقارنة - الهنائي، عبدالله بن سالم بن حمد (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2020)
يهدف البحث إلى إبراز معنى القراءات الشاذة وأهم المؤلفات فيها، والتعريف بالسمين الحلبي وكتابه الدر المصون، كما يهدف إلى الكشف عن منهج السمين الحلبي في تعامله مع القراءات الشاذة من خلال جزء تبارك أنموذجا. من خلال الأهداف السابقة تكمن مشكلة الدراسة في الأسئلة الآتية: ما هي القراءات الشاذة؟ ومن هو السمين الحلبي وما أهمية كتابه الدر المصون؟ وما منهجه فيه في القراءات الشاذة؟ وما هي نقاط الضعف والقوة عنده؟ اتبع الباحث المنهج الاستقرائي من خلال تتبعه لجزء تبارك في كتاب الدر المصون للسمين الحلبي، كما اتبع المنهج النقدي في إظهار ما للرجل وما عليه. تكون هذا البحث من ثلاثة مباحث، فالمبحث الأول التعريف بالقراءات الشاذة وحكم العمل بها، والمبحث الثاني التعريف بالسمين الحلبي، أما ثالث المباحث فكان بعنوان منهج الإمام السمين الحلبي في التعامل مع القراءات الشاذة. أبرز ما توصلت إليه الدراسة من نتائج أهمها: القراءات الشاذة هي القراءات التي فقدت أحد أركان القراءة الصحيحة، وهي ما وراء العشرة. - أحسن الإمام السمين الحلبي في تعامله مع القراءات الشاذة من حيث نسبتها إلى أهلها وتوجيهها. - ذكر السمين الحلبي مائة وستة وثلاثين موضعا في جزء تبارك (136) وقد أخذت سورة الجن نصيب الأسد بواحد وعشرين (21) موضعا، بينما أخذت سورة الملك العدد الأقل بستة مواضع فقط. - يؤخذ على السمين الحلبي عدم دقة نسبة بعض القراءات إلى أصحابها وأحيانا عدم نسبة القراءة إلى القائل بها أصلا.
The abnormal readings of As Sameen Al Halabi in his book Al Dur Al Masoun. Part of Tabarak as a model. A theoretical, comparative study. The research aims to highlight the meaning of abnormal readings and the main publications on it. It also aims to introduce As Sameen Al Halabi and his book Al Dur Al Masoun, especially in terms of the approach he followed to deal with abnormal readings by focusing on the part of Tabark as a model. The main questions of the study are: what are the abnormal readings? Who is As Sameen Al Halabi and what is the importance of his book Al Dur Al Masoun? What is his approach in dealing with abnormal readings? And what are his strengths and weaknesses? The researcher followed an inductive approach to research where he examined As Sameen Al Halabi’s methods in abnormal readings in Tabarak; the researcher used a critical approach to investigate the strengths and weaknesses in Al Halabi’s approach. The research consisted of three parts: Part one introduced the concept of abnormal readings; Part two introduced As Sameen Al Halabi and his works, and Part three focused on As Sameen Al Halabi’s approach in dealing with abnormal readings. The main results of the study are: -Abnormal readings are those that missed one of the main components of accurate readings. -Imam As Sameen Al Halabi dealt effectively with abnormal readings especially in terms of attributing them to their original readers and justifying them. As Sameen Al Halabi found 136 areas of abnormal readings in Tabarak, where surat Al Jin had the lion’s share of (21) areas whereas Al Mulk had the least (6 areas). One criticism of As Sameen Al Halabi is the inaccuracy in attributing some readings to their actual readers and in some cases not mentioning the original reader.
Keywords: القرآن الكريم -- القراءات الشاذة -- السور والآيات -- السمين الحلبي، أحمد بن يوسف بن محمد بن مسعود، ت. 756 هـ